Energy Analysis on the Processing of Green Tea - Wahyu K Sugandi; Kralawi Sita; Totok Herwanto; Shida Habsari (The University of Lampung, 2022)
Energy analysis on processing of green tea at green tea factory. Research Institute for Tea and Cinchona (RITC) Gambung was conducted to analyze energy use and identify energy use. Energy analysis is calculated based on the use of biological energy, direct energy, and indirect energy at each process of green tea processing started from withering to packaging activities. This research was conducted with descriptive analysis method by measure and calculate the energy usage for each process. The results showed that the total of energy use in green tea 51.141 MJ/kg. Indirect energy is the biggest energy contributor to the use of total energy (with indirect energy) with energy values reached 46.764 MJ/kg. Meanwhile, the total use of biological energy is 0.01 MJ/kg and the total use direct energy is 4.366 MJ/kg. The results of the energy analysis assestment show that energy savings can be made by maintaining and replacing the damaged parts of the machine especially maintenance of burner in withering process, changing the concept of tea packing to 55 kg of tea/pack, changing the capacity of ball tea machine in the second drying process to 400 kg of dry tea to save the electricity supply system. The results of SWOT analysis showed in quadrant I, where the strategy in this quadrant is S-O strategy, which is growth-oriented strategy. Keywords: Energy analysis, Energy saving, Green tea, Processing of tea, SWOT